2021
DOI: 10.1097/ta.0000000000003174
|View full text |Cite
|
Sign up to set email alerts
|

Can educational videos reduce opioid consumption in trauma inpatients? A cluster-randomized pilot study

Abstract: BACKGROUND:Opioids are often used to treat pain after traumatic injury, but patient education on safe use of opioids is not standard. To address this gap, we created a video-based opioid education program for patients. We hypothesized that video viewing would lead to a decrease in overall opioid use and morphine equivalent doses (MEDs) on their penultimate hospital day. Our secondary aim was to study barriers to video implementation. METHODS:We performed a prospective pragmatic cluster-randomized pilot study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The 36 included studies took place in 16 different countries: 19 (52.8%) in Europe [ 22 , 25 , 28 33 , 35 , 36 , 38 , 41 , 46 , 48 , 52 54 , 56 , 57 ], 11 (30.6%) in North America [ 23 , 24 , 26 , 27 , 34 , 39 , 43 , 44 , 49 51 ], four (11.1%) in Asia [ 40 , 42 , 47 , 55 ], and two (5.6%) in Australia [ 37 , 45 ]. The general characteristics of the selected studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 36 included studies took place in 16 different countries: 19 (52.8%) in Europe [ 22 , 25 , 28 33 , 35 , 36 , 38 , 41 , 46 , 48 , 52 54 , 56 , 57 ], 11 (30.6%) in North America [ 23 , 24 , 26 , 27 , 34 , 39 , 43 , 44 , 49 51 ], four (11.1%) in Asia [ 40 , 42 , 47 , 55 ], and two (5.6%) in Australia [ 37 , 45 ]. The general characteristics of the selected studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 49 ] 2017 USA Primary care NA Opioids Patient information + motivational interviewing with patient 8.5 Tannenbaum C. [ 50 ] 2014 Canada Primary care 65 BZD Patient empowerment intervention 6 Tseng ES. [ 51 ] 2021 USA Hospital, trauma unit NA Opioid Patient information 1 Van der Meer HG. [ 52 ] 2018 Netherlands Primary care 65 Anticholinergic and sedative drugs Medication drug review (pharmacist) 3 Vicens C. [ 53 ] 2014 Spain Primary care NA BZD GP information 12 Vicens C. [ 54 ] 2016 Spain Primary care NA BZD GP information 36 Wong APY.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As hypothesized, after the educational intervention, we observed reductions in prescribed opioids directly related to the shift in attitudes toward opioids. In addition, another recent pilot study employed video-based education on opioid safety for patients after traumatic injury ( 21 ). The authors found that among the patients who were continuously using opioids throughout the study, the group who watched the educational video had lower MME than the group who did not receive an educational information ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted an educational intervention to change expectations and perceptions toward opioids safety. Unlike a recent study using pre-recorded video education with a low participant compliance ( 21 ), the educational intervention in the current study was conducted by trained research staff, ensuring interactive educational procedures rather than passive learning. Moreover, the research staff was independent of the clinical treating team of nurses and physicians, minimizing recruitment and other biases.…”
Section: Discussionmentioning
confidence: 99%